2000
DOI: 10.1046/j.1523-1755.2000.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipids and risk of developing renal dysfunction: The Atherosclerosis Risk in Communities Study

Abstract: High triglycerides and low HDL cholesterol, but not low-density lipoprotein cholesterol, predict an increased risk of renal dysfunction. The treatment of these lipid abnormalities may decrease the incidence of early renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
401
6
15

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 597 publications
(461 citation statements)
references
References 44 publications
39
401
6
15
Order By: Relevance
“…Our results and the REGARDS study are consistent with the considerable body of literature reporting no association between total blood cholesterol and chronic kidney disease risk, with the possible exception of triglycerides and high‐density lipoprotein cholesterol 22, 23, 24. Unlike our study, the risk of end‐stage renal disease was not significantly associated with body mass index or smoking.…”
Section: Discussionsupporting
confidence: 90%
“…Our results and the REGARDS study are consistent with the considerable body of literature reporting no association between total blood cholesterol and chronic kidney disease risk, with the possible exception of triglycerides and high‐density lipoprotein cholesterol 22, 23, 24. Unlike our study, the risk of end‐stage renal disease was not significantly associated with body mass index or smoking.…”
Section: Discussionsupporting
confidence: 90%
“…In studies of patients with CKD (12) and without CKD (8), LDL-C and ApoB were significantly associated with a more rapid decline in renal function. Our study found no statistically significant association between LDL-C or apoB and CKD progression in the overall CRIC population, consistent with the Modification of Diet in Renal Disease and Atherosclerosis Research in Communities (ARIC) studies, as well as the Study of Heart and Renal Protection (SHARP) clinical trial, where statin/ezetimibe therapy was not associated with reduction in progression of kidney disease (9,11,27,28) However, total and LDL-C cholesterol levels were inversely associated with progression of kidney disease in patients with low levels of proteinuria, particularly those receiving statin therapy. The factors underlying this seemingly paradoxical relationship are unclear; participants in the lower cholesterol quartiles had more risk factors for progression and were more likely to be taking statins, perhaps reflecting a higher vascular risk.…”
Section: Discussionsupporting
confidence: 84%
“…Animal studies have shown development and progression of kidney damage in the setting of hyperlipidemia with increased glomerulosclerosis and tubulointerstitial damage (3)(4)(5)(6). In epidemiologic studies, the presence of dyslipidemia was associated with a higher risk of development of incident CKD in the general population (7)(8)(9). The association between dyslipidemia and progression of established kidney disease is not consistent in studies of diabetic (10) and nondiabetic (11)(12)(13)(14)(15) participants.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of 30 overweight patients and various nephropathies, a mean weight loss of 4.1% in the diet group was associated with a 31.2% reduction in proteinuria [7].…”
Section: Definition Of Chronic Kidney Diseasementioning
confidence: 95%
“…The deterioration is often attributed to systemic hypertension, proteinuria, hyperlipidaemia [3,4], and intra glomerular hypertension [5]. Smoking, obesity and anaemia are considered other risk factors for progression of chronic kidney disease [6][7][8].…”
Section: Definition Of Chronic Kidney Diseasementioning
confidence: 99%